A robotic platform for high-throughput electrochemical analysis of chalcopyrite leaching - Albrecht,T; Godfrey,D; Bannock,JH; Kuzmina,O; Welton,T (Green Chemistry, 2016)
Cu extraction from chalcopyrite ores is typically a slow process that involves aggressive chemical reagents with significant environmental impact. Ionic liquids (IL) have been proposed as a potentially more benign solution, but the sheer number of IL variants complicates the search for the most efficient solvent systems. Here, we present an automated electrochemical platform that allows for screening of 180 and more leaching samples in parallel with minimal solvent consumption. In a proof-of-concept study, we screen 25 samples with different IL and water contents, and find two orders of magnitude difference in leaching performance within this array. The best performing system is then applied in a tank leaching configuration, with real-time electrochemical monitoring of Cu evolution in solution. All electrochemical data is found to be in excellent agreement with off-line ICP-AES data.